Cu–MoS2 Superhydrophobic Coating by Composite Electrodeposition - Prado, Lucia; Virtanen, Sannakaisa (Coatings, 2020)
In this work, a superhydrophobic coating was developed by composite electrodeposition of MoS2 particles in a copper matrix. AISI 316L stainless steel and N80 carbon steel, with a thin electrodeposited Ni layer to improve adherence of the coating, were used as substrates. Different operational parameters of electrodeposition were studied in order to produce the highest possible contact angle. We demonstrate that, using this method, a coating with a hierarchical structure with feature dimensions in the range of µm to nm is obtained, with advancing contact angle values up to 158.2° and a contact angle hysteresis equal to 1.8°. To study the coating composition energy dispersive X-ray, X-ray photoelectron spectroscopy and time-of-flight secondary ion mass spectrometry were performed. Moreover, potentiodynamic polarizations were performed in H2SO4, NaCl and NaOH solutions to study the corrosion behavior of the coating. As a control, a sample coated only with MoS2 particles by means of electrophoretic deposition was produced. The results show that the composite coating can be used in applications where copper is used for corrosion protection, with the addition of the desirable effects of its superhydrophobicity.
Keywords: Superhydrophobic; Composite electrodeposition; Electrophoretic deposition; Corrosion; Composite coating; Wettability